The Foreign experiences of оnline learning in journalism education. (Herald of Journalism, 2016)
The paper aims to analyze the Online-learning process in the example of courses by the Coursera. The author analyses the key standards of оnline-learning in the modern society. Coursera is an education company that partners with the top universities and organizations in the world to offer courses online for anyone to take, for free. The paper argues that while оnline-learning process may seem challenging, the outcome of the work will bring many opportunities to the education process.
Keywords: Online learning; journalism education; innovation and technology; new standards; academic journalism programs.